2020
DOI: 10.3390/ijerph17165708
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Assess Inhalation Exposures among Sugarcane Workers in Guatemala: Implications for Chronic Kidney Disease of Unknown Origin

Abstract: Background: Sugarcane workers in Central America experience a heavy burden of chronic kidney disease of unknown origin. We conducted a pilot study among worker proxies in Guatemala to characterize exposures to particulate matter, silica, heavy metals, and glyphosate, as well as to examine potential nephrotoxic exposures. Methods: Air, soil, and ash samples were collected and analyzed using scanning electron microscopy, X-ray diffraction, inductively coupled plasma mass spectrometry, and an enzyme-linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 67 publications
(78 reference statements)
0
8
1
4
Order By: Relevance
“…This study demonstrated that a significant percentage of employees in Ethiopia’s Metehara and Wonji sugar factories were exposed to a significant amount of bagasse dust that exceeded the recommended limit, resulting in a considerable burden of chronic respiratory ailments. When compared with research conducted in China,42 Pakistan,43 Thailand,2 UK,1 India,44 45 Central America46 and Brazil,47 48 this study discovered a higher level of bagasse dust exposure. The possible explanations for this disparity could be related to the different techniques of controlling dust emissions at their sources, the nature of the machines used, the organisational safety infrastructure, and the sample sizes and sampling strategies used.…”
Section: Discussioncontrasting
confidence: 56%
“…This study demonstrated that a significant percentage of employees in Ethiopia’s Metehara and Wonji sugar factories were exposed to a significant amount of bagasse dust that exceeded the recommended limit, resulting in a considerable burden of chronic respiratory ailments. When compared with research conducted in China,42 Pakistan,43 Thailand,2 UK,1 India,44 45 Central America46 and Brazil,47 48 this study discovered a higher level of bagasse dust exposure. The possible explanations for this disparity could be related to the different techniques of controlling dust emissions at their sources, the nature of the machines used, the organisational safety infrastructure, and the sample sizes and sampling strategies used.…”
Section: Discussioncontrasting
confidence: 56%
“…Exposures may also be coming from contaminants in the air, soil, and ash due to sugarcane burning practices. 56 Interestingly, a previous study conducted within a population of first-year sugarcane workers in the same region observed that workers who reported using a well water source at home had 6.1 times the odds of being in the subgroup that had lower kidney function at the start of their first year and had greater declines in kidney function over the harvest compared to all other sources of home water. 22 A few other studies have observed renal impairment among agricultural workers who are chronically exposed to glyphosate and paraquat.…”
Section: Discussionmentioning
confidence: 95%
“…Os trabalhadores do corte de cana-de-açúcar estão sujeitos também a exposição a poluentes. A colheita manual da cana-de-açúcar anteriormente era precedida pela queima da Rev Cient da Fac Educ e Meio Ambiente: Revista Científica da Faculdade de Educação e Meio Ambiente -FAEMA, Ariquemes, v. 14, n. 1, p. 69-83, 2023. palha para retirada a folhagem morta e facilitar o corte, processo esse que contribui para a poluição do ar local e produz uma espessa camada de cinzas no solo na base das plantas (14) .…”
Section: Corte Manual Da Cana-de-açúcar E Riscos Para O Trabalhadorunclassified
“…Além dos perigos potenciais dessa Rev Cient da Fac Educ e Meio Ambiente: Revista Científica da Faculdade de Educação e Meio Ambiente -FAEMA, Ariquemes, v. 14, n. 1, p. 69-83, 2023. substância para a saúde respiratória, os trabalhadores estão também potencialmente em risco de lesão renal induzida por sílica, sendo esse mineral frequentemente citado como um fator de risco potencial para doença renal crônica de origem desconhecida. Ademais, além da sílica, os trabalhadores da cana-de-açúcar estão expostos a outros nefrotóxicos e contaminantes presentes na fuligem, como resíduos de agrotóxicos e metais pesados (14) . Além de todos esses problemas já elencados, estudos também apontam os danos cromossômicos presentes em cortadores de cana-de-açúcar e derivados da realização dessa atividade.…”
Section: Corte Manual Da Cana-de-açúcar E Riscos Para O Trabalhadorunclassified